PENDEKATAN DIAGNOSIS DAN TERAPI FIBROSIS HATI - Anom S, Tjok Istri; Wibawa, I Dewa Nyoman (journal of internal medicine, 2012)
Liver Þ brosis is the excessive accumulation of extracellular matrix proteins including collagen that occurs in most types of chronic liver. The gold standard to assess disease severity of liver Þ brosis is liver biopsy, despite noninvasive methods available today. A noninvasive tool (Þ bro scan) has been developed these days. This tool is similar to ultrasound in assessing liver elasticity. There are three methods frequently used to assess liver Þ brosis, Ishak score, Metavir score, and Desmet/Scheuer staging system. The principles of antiÞ brotic therapy are: (a) to treat primary disease; (b) to reduce inß ammation response or to avoid stimulation of stellate cell activation; (c) to reduce stellate cell activation; (d) to neutralize proliferation response, Þ brogenic response, contractic response, and/or stellate cell proinß ammation; (e) to stimulate apoptosis of stellate cell; and (f) to increase degradation of Þ brotic tissue.
Keywords: liver Þ brosis, Þ bro scan, antiÞ brotic therapy